Critical parameters controlling the properties of monolithic poly(lactic acid) foams prepared by thermally induced phase separation. Issue 2 (20th November 2018) - Onder, Ozgun Can; Yilgor, Emel; Yilgor, Iskender
ABSTRACT: Monolithic poly(lactic acid) (PLA) foams were produced by thermally induced phase separation. PLA solutions with concentrations 8–22 wt % were prepared in tetrahydrofuran/methanol (THF/MeOH) solvent/nonsolvent mixtures at 55 °C. Homogenous solutions were quenched at −20 °C to induce phase separation and gelation. Resulting gels were mechanically stabilized by solvent exchange. Subsequent supercritical CO2 drying yielded monolithic PLA foams. Crystal structure and degree of crystallinity of the foams were obtained by x‐ray diffractometry and differential scanning calorimetry. Morphologies were determined by scanning electron microscopy. Tuning the PLA concentration and THF/MeOH ratio enabled preparation of monolithic PLA foams. Depending on the experimental conditions various morphologies, such as: interconnected networks, thin platelets, lamellar stacks, axialites, and spherulites were formed. Monoliths obtained were highly crystalline. By changing the PLA concentration monoliths with controlled average pore sizes (170–1440 nm) and porosities (80–90%) were produced. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2019, 57, 98–108 Abstract : Poly(lactic acid) (PLA) foams were produced by thermally induced phase separation. PLA solutions prepared in tetrahydrofuran/methanol mixtures were quenched at −20 °C to induce phase separation and gelation. Gels were stabilized by solvent exchange and supercritical CO2 drying to obtain monolithic foams. Structure, morphology and crystallinity of the foams were investigated by XRD, DSC and SEM. By changing PLA concentration and solvent composition crystalline monoliths with different pore sizes (170–1440 nm) and porosities (80–90%) were produced.